2019
DOI: 10.3390/genes10110911
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Analysis of Members of the WRKY Gene Family and Their Cold Stress Response in Prunus mume

Abstract: Prunus mume, which is a rosaceous arbor with very high ornamental, edible and medical values, has a distribution that is mainly restricted by low temperature. WRKY transcription factor genes play crucial roles in the growth, development, and stress responses of plants. However, the WRKY gene family has not been characterised in P. mume. There were 58 PmWRKYs identified from genome of P. mume. They were anchored onto eight link groups and categorised into three broad groups. The gene structure and motif composi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 42 publications
(62 reference statements)
11
20
0
Order By: Relevance
“…The rate of gene duplication in this study was lower than in other plants, suggesting gene duplication was the secondary formation in PmbHLH gene expansion or PmbHLHs, and that loss-functions or redundancies may be lost during evolution. This conclusion was similar to the PmWRKY genes family (Bao et al, 2019).…”
Section: Discussionsupporting
confidence: 84%
“…The rate of gene duplication in this study was lower than in other plants, suggesting gene duplication was the secondary formation in PmbHLH gene expansion or PmbHLHs, and that loss-functions or redundancies may be lost during evolution. This conclusion was similar to the PmWRKY genes family (Bao et al, 2019).…”
Section: Discussionsupporting
confidence: 84%
“…Based on our study and similar work in other croppathogen systems, we predict that these GbCNL genes in cotton may provide resistance to various pathogens, including V. dahliae. Transcriptome analysis has also been used to identify candidate genes involved in disease resistance of several species, including G. barbadense Bao et al, 2019). Our transcriptome analysis showed that ten GbCNL genes, including six GbCNLs from two largest clusters (GC11 and GC12), are significantly upregulated after V. dahliae inoculation, supported by RT-qPCR analysis of multiple candidate genes.…”
Section: Discussionmentioning
confidence: 61%
“…Transcriptome analysis has also been used to identify candidate genes involved in disease resistance of several species, including G. barbadense ( Yang and Wang, 2016 ; Bao et al, 2019 ). Our transcriptome analysis showed that ten GbCNL genes, including six GbCNL s from two largest clusters (GC11 and GC12), are significantly upregulated after V. dahliae inoculation, supported by RT-qPCR analysis of multiple candidate genes.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, MYB and TCP TFs were found to express more and earlier in the cold-sensitive sugarcane varieties compared to the cold-tolerant varieties [ 32 ]. WRKY TFs were significantly changed in multiple tissues and identified to regulate cold resistance in Prunus mume [ 33 ]. In the present study, we observed that 4 TF subtypes (e.g., HSF domain class, WRKY, ethylene-responsive, and TCP4) were regulated by 5 miRNAs (Supplementary Table S4 ), including miR1886, miR2084, miR6135, miR8036, and gma-miR1520o-3p.…”
Section: Discussionmentioning
confidence: 99%